2020
DOI: 10.1017/s0030605319001376
|View full text |Cite
|
Sign up to set email alerts
|

Does REDD+ have a chance? Implications from Pemba, Tanzania

Abstract: Conservation scientists continue to debate the strengths and weaknesses of REDD+ as an instrument to slow greenhouse gas emissions in the developing world. We propose that general positions on this debate are less helpful than drawing lessons from specific investigations into the features of individual projects that make them successful or not. Here, focusing on a site-specific REDD+ intervention in Pemba, Zanzibar (Tanzania), we examine the circumstances under which REDD+ has a chance of success, teasing out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Approaches developed thus far include payments for ecosystem services (PES) and reducing emissions through deforestation and forest degradation (REDD). While huge investments have been made especially in REDD (and REDD +), progress has been slow (Clements 2010;Brockhaus et al 2015;Börner et al 2017;Ferraro 2017;Milbank et al 2018;Andrews et al 2020). An approach that has not been well explored is using inclusive finance and community savings and loan models to incentivize ecosystem management or restoration activities.…”
Section: The Need For Green Inclusive Finance To Incentivize Adaptation Actions Of Rural Producersmentioning
confidence: 99%
“…Approaches developed thus far include payments for ecosystem services (PES) and reducing emissions through deforestation and forest degradation (REDD). While huge investments have been made especially in REDD (and REDD +), progress has been slow (Clements 2010;Brockhaus et al 2015;Börner et al 2017;Ferraro 2017;Milbank et al 2018;Andrews et al 2020). An approach that has not been well explored is using inclusive finance and community savings and loan models to incentivize ecosystem management or restoration activities.…”
Section: The Need For Green Inclusive Finance To Incentivize Adaptation Actions Of Rural Producersmentioning
confidence: 99%
“…Despite some clear successes (Jarrah, 2014), HIMA failed to achieve its major goal of securing carbon revenue (Royal Norwegian Embassy, 2015b), paralleling the outcome at all other pilot REDD+ sites across Tanzania (Royal Norwegian Embassy, 2015a; Sunderlin et al, 2015). Furthermore, several measures indicate that, without carbon payments, deforestation continued apace on the island: (a) overall forest extent on Pemba (protected areas excluded) was 25% in 2001 but had declined to 15% by 2018, (b) median forest cover change across the island was −3.1%/year for 2001-2010, but −3.4%/year for 2010-2018, (c) ward-level rates of forest cover change were generally negative, with 89% of wards experiencing a reduction in forest area during 2001-2010 and 75% during the 2010-2018 period (Collins, 2020), and (d) a comparison of baseline rates of deforestation in the first period to rates in the second period shows that of the 18 Pemban shehia that had registered CoFMAs, six had managed to slow their rates of net deforestation in the latter period and two had greater forest cover in 2018 than 2010 (i.e., they had reversed the trend, Andrews et al, 2020).…”
Section: Current Challengesmentioning
confidence: 99%
“…Comparing baseline rates of deforestation (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) to current rates (2010-2018) showed that of the 18 Pemban shehia with registered CoFMAs, six had slowed their rates of net deforestation since the onset of the HIMA project, and two had greater forest cover in 2018 than 2010 (Andrews et al, 2020). This prompted an analysis of the variation in that performance, to determine whether the institutional quality of the SCC was associated with forest cover change between 2010 and 2018.…”
Section: Institution Performance Rankings and Reduced Deforestationmentioning
confidence: 99%
See 2 more Smart Citations